Effect of Pore Structure on Performance of Porous Metal Fiber Materials. Issue 8 (August 2015) - Huiping, Tang; Jianzhong, Wang; Qingbo, Ao; Hao, Zhi
Abstract: The pore structure of porous metal fiber materials is a key factor affecting their performances, so the effects of the pore structure on the performances were analyzed in the paper. Using FeCrAl fiber as starting materials, porous metal materials were prepared by an air flow method and sintering process. The microstructures of sintered samples were observed by a scanning electron microscope (SEM). The tensile strength and air permeability were also tested. The sound absorption coefficients at 90–140 dB with different frequencies from 1000–3000 Hz were measured. In addition, the fractal dimension of the pore structure was calculated by self-developed software which was based on the fractal theory and computer image processing technology. The effects of pore structure on the tensile strength, the sound absorption coefficient and the air permeability were discussed, and the relationships among the tensile strength, the air permeability and the fractal dimension were described. Results show that the tensile strength decreases linearly with the fractal dimension increasing, while the air permeability increases obviously. Additionally, the sound absorption coefficient declines gradually with the fractal dimension increasing at the same sound intensity or frequency.